1998
DOI: 10.1038/sj.onc.1202073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two distinct tumor-suppressor loci on the long arm of chromosome 10 in small cell lung cancer

Abstract: Recent cytogenetic studies indicated that loss of the long arm of chromosome 10 is a frequent event in small cell lung cancer (SCLC) and that a common region of the deletion is at 10q24-qter, which suggests the presence of a tumor-suppressor gene there. To map precise tumorsuppressor loci on the chromosome arm for further positional cloning e orts, we tested 46 primary SCLCs using microsatellite analysis. By analysing 11 highly polymorphic microsatellite markers located in 10q23-q26, we found that at least 78%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 20 publications
(27 reference statements)
5
73
0
Order By: Relevance
“…In an e ort to ®nd a molecular correlate for the markedly malignant phenotype of SCLC, genetic alterations and abnormal expression patterns of many oncogenes and tumor suppressor genes have been investigated. Multiple chromosomal deletions on 3p, 4q, 5q, 9p, 10q, 13q and 17p as well as DNA over-representations on 3q and 5p have been found in primary tumors and their metastases (Kim et al, 1997;Petersen et al, 1997;Cook et al, 1993). Several tumor suppressor genes have been found to be altered frequently in SCLC including RB whose protein expression is absent or truncated in the majority of tumors and cell lines and p53 which is mutated in more than 80% of tumors and cell lines (Harbour et al, 1988;Rygaard et al, 1992;D'Amico et al, 1992;Miller et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In an e ort to ®nd a molecular correlate for the markedly malignant phenotype of SCLC, genetic alterations and abnormal expression patterns of many oncogenes and tumor suppressor genes have been investigated. Multiple chromosomal deletions on 3p, 4q, 5q, 9p, 10q, 13q and 17p as well as DNA over-representations on 3q and 5p have been found in primary tumors and their metastases (Kim et al, 1997;Petersen et al, 1997;Cook et al, 1993). Several tumor suppressor genes have been found to be altered frequently in SCLC including RB whose protein expression is absent or truncated in the majority of tumors and cell lines and p53 which is mutated in more than 80% of tumors and cell lines (Harbour et al, 1988;Rygaard et al, 1992;D'Amico et al, 1992;Miller et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many lung cancers may have lost a whole chromosome 9 (Merlo et al, 1994a and1994b). Our recent study revealed at least three distinct minimally deleted regions at 9p in SCLCs (Kim et al, 1997), and one of the regions is close to the region of the PTH2 gene. LOH analysis of primary SCLCs using extensive microsatellite markers close to PTH2 should provide further information.…”
Section: Discussionmentioning
confidence: 78%
“…The short arm of chromosome 9 is frequently deleted in many types of human cancer, including SCLC and non-small cell lung cancer (NSCLC) (Kim et al, 1997;Merlo et al, 1994a, b). Although the p16 tumor suppressor gene located at 9p21 is inactivated in many human cancers (Nobori et al, 1994;Kamb et al, 1994;Merlo et al, 1995;Cairns et al, 1995), the presence of other tumor suppressor genes in chromosome 9 has been suggested (Kim et al, 1997;Ohta et al, 1996b;Wiest et al, 1997). In fact, many lung cancers may have lost a whole chromosome 9 (Merlo et al, 1994a and1994b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 More than 89% of lung tumors were found to exhibit loss of heterozygosity on 9p, with 3 distinct deleted areas, suggesting the presence of at least 3 novel tumor suppressor loci on 9p in SCLC. 11 Several well-characterized tumor suppressor genes (TSGs), including p16/ CDKN2, MTAP, P16␤ and p15, have been mapped to 9p. In addition, the new putative tumor suppressor gene TSC1, mapped to 9q, might be involved in lung adenocarcinoma.…”
mentioning
confidence: 99%